2020
DOI: 10.1016/j.ymgmr.2020.100667
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Gaucher disease display systemic oxidative stress dependent on therapy status

Abstract: Gaucher disease is an autosomal recessive metabolic disorder caused by mutations in GBA1 , which encodes for the lysosomal hydrolase enzyme, β-glucocerebrosidase. The resulting misfolded protein can trigger endoplasmic reticulum stress and an unfolded protein response within the affected cells. The enzyme deficiency leads to accumulation of its substrates, glucosylceramide and glucosylsphingosine, within macrophage lysosomes and with prominent disease manifestations in macrophage rich ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The CAT gene encodes catalase, a key antioxidant enzyme that protects aerobic cells from reactive oxygen species (ROS). GD patients are primed for oxidative response complications because they are known to have a severe redox imbalance partially caused by alterations in catalase activity [ 44 ]. While plasma from GD patients has elevated catalase enzymatic activity, GD RBCs have significantly lower catalase activity [ 18 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CAT gene encodes catalase, a key antioxidant enzyme that protects aerobic cells from reactive oxygen species (ROS). GD patients are primed for oxidative response complications because they are known to have a severe redox imbalance partially caused by alterations in catalase activity [ 44 ]. While plasma from GD patients has elevated catalase enzymatic activity, GD RBCs have significantly lower catalase activity [ 18 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of MDA and the enhancement of MPO activity will accelerate the in ltration of neutrophils in the kidney tissue and promote the progress of in ammation [38] [39]. As effective antioxidants, SOD and GSH-Px are equally important in response to oxidative stress and regulating the redox state of cells [37,[40][41][42]. Studies also showed that Nrf2, an important antioxidant pathway, protect cells from in ammation through regulation of oxidative stress [43].…”
Section: Discussionmentioning
confidence: 99%
“…According to the impairment of central nervous system function, there are three GD types ( Carubbi et al, 2020 ). Gaucher disease type 1 (GD1) was regarded as the mildest form without obvious neurologic involvement at an early stage, but some GD1 patients developed Parkinson disease phenotype at older age ( Kartha et al, 2020 ). Type 2 is the most severe form and appears as an early onset of neurologic disease with an acute course.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 is the most severe form and appears as an early onset of neurologic disease with an acute course. Type 3 disease is of intermediate severity with a later onset of neurologic symptoms and a more chronic course ( Kartha et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%